Rethinking political foundations with Leo Strauss, Hannah Arendt and Eric Voegelin - Trimcev, E (2013)
The problem of understanding political foundings is situated at the nexus between political philosophy and political science. This thesis rethinks founding by asking both the philosophical question of how political order comes into being, and the political science question of how to understand particular founding moments. These two questions stimulate and structure a dialogue between the works of Leo Strauss, Hannah Arendt and Eric Voegelin. The approach of founding in all three has a common starting point: they begin from ordinary experience and outline a political science that is mindful of the phenomenality of political life. I show that Strauss’s return to ordinary experience is partial. By limiting political life to the normative claims raised in it and submitting them to philosophical judgment, Strauss moves too quickly beyond political phenomena. His account of founding, as a consequence, vacillates between understanding particular founding acts and conceiving the perfect founding moment in abstract thought. Arendt’s work decisively shifts the problem on the side of practical understanding. Yet, her ontological account of action as appearance subtly displaces her concern for understanding historical actions. I move away from approaching historical foundings as a mode of appearing in the world, by recovering an account of action as experience. On that basis, I suggest a hermeneutics of experience which approaches foundings in light of the quest for meaning. With Voegelin founding is recovered as a symbol that exists only in the quest of understanding. Founding occurs in the experience of struggle to restore a reality that has become symbolically opaque. This experience is shared by the philosopher and the political actor; therefore to understand moments of founding requires the interweaving, and not separation, of political philosophy and political science. At the end, the quest of understanding founding moments is neither derivative, nor preparatory, but encompassing the philosophical question of how order comes into being.